2004
DOI: 10.1111/j.0036-9292.2004.05101008.x
|View full text |Cite
|
Sign up to set email alerts
|

Productive Efficiency and Salary Distribution: The Case of US Major League Baseball

Abstract: Recent theoretical research suggests that a firm's salary structure can affect the firm's productivity. We investigate the relationship between payroll inequality and production using US Major League Baseball data. Employing panel data methods, this study finds that salary inequality has a significantly negative effect on team success. A general result is that team success in term of wins does not seem to be correlated with efficiency; specifically, some of the least successful teams are also some of the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 30 publications
(25 reference statements)
3
32
0
Order By: Relevance
“…He found that greater player pay dispersion was negatively related to both team and individual performance. Using essentially the same baseball sample used in Bloom (1999) but with a more extensive set of econometric specifications, Jewell & Molina (2004), Depken (2000), and Frick et al (2003) also found a negative relationship between pay dispersion and on-field performance. Jane and colleagues (Jane 2010, Jane et al 2009, San & Jane 2008 found similar negative relationships between pay dispersion and team performance in a series of studies in the Taiwanese professional baseball league.…”
Section: Team Performancementioning
confidence: 90%
“…He found that greater player pay dispersion was negatively related to both team and individual performance. Using essentially the same baseball sample used in Bloom (1999) but with a more extensive set of econometric specifications, Jewell & Molina (2004), Depken (2000), and Frick et al (2003) also found a negative relationship between pay dispersion and on-field performance. Jane and colleagues (Jane 2010, Jane et al 2009, San & Jane 2008 found similar negative relationships between pay dispersion and team performance in a series of studies in the Taiwanese professional baseball league.…”
Section: Team Performancementioning
confidence: 90%
“…Therefore, club-level efficiency has become the key to winning when each club has a similar fighting capacity. Jewell and Molinan (2004) found that a resourceabundant club in a 'large-market' can still be very successful regardless of inefficiency. However, in this paper we show that club-level efficiency does have an impact on club performance.…”
Section: Resultsmentioning
confidence: 99%
“…However, the correlation coefficients for all measurements were rather small. Unlike Jewell and Molinan (2004), in this study we try to estimate club-level efficiency based on batters' individual technical efficiencies. As we discussed above, we are aiming to see if club-level efficiencies have a significant impact on clubs' winning percentages.…”
Section: Club-level Efficiencymentioning
confidence: 99%
See 2 more Smart Citations